PENGARUH PPN, PPnBM, DAN PKB TARIF PROGRESIF PADA DAYA BELI KONSUMEN KENDARAAN BERMOTOR RODA EMPAT - Pramesti, Devi; Supadmi, Ni Luh (E-Jurnal Akuntansi, 2017)
Sources of income countries have a considerable influence on the development of a country is a tax. Taxes collected will be used for the construction of a negara.Tujuan study was to determine the effect of VAT, luxury sales, and vehicle tax with progressive rates on consumer purchasing power automobiles. Research conducted at the office of the Joint SAMSAT and Showroom in Denpasar 2016. The research sample of 100 people from the 209 261 people who constitute the whole taxpayers make tax payments at the office SAMSAT Joint Denpasar in 2015 and potential consumers in Showroom in Denpasar obtained by the method nonprobability sampling with purposive sampling technique. Data analysis techniques that multiple linear regression analysis. The results of analysis, the imposition of VAT and sales tax on luxury has a significant positive effect, and vehicle tax with progressive rates have a significant negative influence on consumers' purchasing power on automobiles.
Keywords: value-added tax, sales tax on luxury goods, motor vehicle tax, the purchasing power